2017
DOI: 10.1515/raon-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic perfusion imaging for the prediction of response and survival to transarterial chemoembolization of hepatocellular carcinoma

Abstract: BackgroundThe purpose of this retrospective cohort study was to evaluate the clinical value of computed tomographic perfusion imaging (CTPI) parameters in predicting the response to treatment and overall survival in patients with hepatocellular carcinoma (HCC) treated with drug-eluting beads transarterial chemoembolization (DEBTACE).Patients and methodsBetween December 2010 and January 2013 eighteen patients (17 men, 1 woman; mean age 69 ± 5.8 years) with intermediate stage HCC underwent CTPI of the liver prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In this study, not only the mean value of perfusion parameters was analyzed, but also the percentiles of histogram analysis were calculated, which might be superior to median values for tumor grading and tumor recurrence evaluation. [ 28 , 31 ] The mean values, and the 10th, 50th, 75th, and 90th percentiles of HAC and AEF were significantly higher than the surrounding liver parenchyma, whereas the mean value, and the 10th, 50th, 75th, and 90th percentiles of PVC were significantly lower in the HCC tumor than the surrounding liver parenchyma, which was in line with previous findings. [ 32 34 ]…”
Section: Discussionsupporting
confidence: 89%
“…In this study, not only the mean value of perfusion parameters was analyzed, but also the percentiles of histogram analysis were calculated, which might be superior to median values for tumor grading and tumor recurrence evaluation. [ 28 , 31 ] The mean values, and the 10th, 50th, 75th, and 90th percentiles of HAC and AEF were significantly higher than the surrounding liver parenchyma, whereas the mean value, and the 10th, 50th, 75th, and 90th percentiles of PVC were significantly lower in the HCC tumor than the surrounding liver parenchyma, which was in line with previous findings. [ 32 34 ]…”
Section: Discussionsupporting
confidence: 89%
“…Bai et al showed that CLTP values in the periphery of HCC lesions correlate with microvascular density on pathology, which is an important prognostic factor for HCC [ 110 ]. Multiple studies have validated CTLP as a non-invasive tool to predict and assess the response of HCC to locoregional and systemic treatment [ 111 , 112 , 113 , 114 , 115 , 116 ]. However, this subject remains out of the scope of this review.…”
Section: Ct Perfusionmentioning
confidence: 99%
“…Similar results were also found by Su et al in HCC patients treated with TACE. Results by Popovic et al 71 revealed that CTp could predict survival in patients with intermediate stage HCC treated with DEB-TACE. However, this technique was not able to assess response to treatment.…”
Section: Resultsmentioning
confidence: 99%